Cooked starchy food in hearths ca. 120 kya and 65 kya (MIS 5e and MIS 4) from Klasies River Cave, South Africa. Issue 131 (June 2019) - Larbey, Cynthia; Mentzer, Susan M.; Ligouis, Bertrand; Wurz, Sarah; Jones, Martin K.
Abstract: Plant carbohydrates currently constitute 55–80% of the modern human diet (FAO and WHO, 1997) and some of today's key global health issues are associated with excessive carbohydrate consumption. However, starch carbohydrate is still a poorly understood element of modern human diet and our past starch diet may provide insights for future research. Despite an archaeological narrative that links our early hominin ancestors to a diet that is rich in roots and tubers, there is little deep time archaeological evidence of human plant starch consumption. Geneticists hypothesise that the duplication of starch digestion genes in early Homo sapiens (∼300 kya), is an adaptive response to an increased starch diet. Here we offer the earliest evidence of identified fragments of charred starch plant tissue (parenchyma) from cave and rock shelter hearths dated to Marine Isotope Stage (MIS) 5e and MIS 4, from the Middle Stone Age (MSA) site of Klasies River main site, South Africa (34.06°S, 24.24°E).